Some psychotherapeutic wisdom in the clinical care of the elderly patient - Edwin Harari (Archive of Gerontology and Geriatrics Research - Peertechz Publications, 2019)
Psychodynamic psychotherapy provides some key principles and cautionary notes which are relevant to the care of the medically-ill elderly patient. Understanding these may improve the clinician-patient relationship, while their neglect them may impair the clinician-patient relationship.